Selenium WebDriver Quick Start Guide : Write Clear, Readable, and Reliable Tests with Selenium WebDriver 3 - Chaubal, Pinakin (Packt Publishing Ltd, 2018)
Selenium WebDriver is a platform-independent API for automating testing of both browser and mobile applications. It is also a core technology in many other browser automation tools, APIs and frameworks. This book will guide you through the WebDriver APIs that are used in automation tests.